Moving beyond agriculture and aquaculture to integrated sustainable food systems as part of a circular bioeconomy - Olesen, Ingrid; Bonaldo, Alessio; Farina, Roberta; Gonera, Antje; Hughes, Adam D.; Navrud, Ståle; Orsini, Francesco; Parma, Luca; Zornoza, Raul (Frontiers in Marine Science, 2023)
The objective of this perspective paper is to present and discuss how systemic innovations can deliver a step change in the way food is produced in Europe. The production of healthy, safe and affordable food can contribute toward a just transition to net zero carbon (C) for Europe. A systemic and cross sectorial approach can contribute to climate mitigation by transfer of atmospheric CO2 to the terrestrial biosphere using low trophic species (LTS), including plants, seaweed and mussels (i.e. C sequestration) and increasing organic C stocks in soils and vegetation biomass (i.e. C storage). Innovative combinations of technologies applied to LTS, processed animal protein, new crops, and diversified and integrated production systems can link the high primary productivity rates of the marine environment to the C storage capability of the terrestrial food sector. Furthermore, the important roles of both private and public sector actors and better use of systemic approaches to further elucidate the multi-dimensional and multi-level interplays in complex food systems needs consideration. This can pave the way for linking and scaling up C-neutral marine and terrestrial food production systems into a future sustainable and circular bioeconomy. This systems-based approach can address some of the challenges associated with the current farming systems, as interdisciplinary research on aquaculture innovation can support the development of a resilient and sustainable food system. Examples of technologies provided include: a custom configured and digital user-oriented co-creation approach for Responsible Research and Innovation (RRI), a WebGIS tool on soil C storage, innovative composting methods, advanced breeding methods, new machinery for low greenhouse gas diversified orchard farming, AI model systems to improve decision support systems in management of soil, vertical farming, and animal feeding.